THE IMPACT OF THE BOYCOTT PHENOMENON ON SWITCHING INTENTIONS FROM FOREIGN FASTFOOD CHAINS TO LOCAL OUTLETS - Salma, Adilah; Rabbaniah, Nadiah; Nuh, Ahmad; Wibowo, Finantyo Eddy (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
This journal aims to analyze the impact of the boycott phenomenon on the intention to switch from foreign fried chicken restaurants such as McDonald's or KFC to local fried chicken restaurants such as D'kriuk or Sabana. Basically, the boycott phenomenon has become a major highlight in boycotting pro-Israel products. This is known from several examples of food products that allegedly provide free food for Zionist soldiers, namely McDonald's and KFC. In addition, the boycott that occurred against this brand was due to its connection with Israel, where there has been a conflict between Palestine and Israel. By boycotting McDonald's or KFC brands that have supported Israeli crimes, we can help stop Israeli aggression against Palestine and fight for the independence and freedom of the Palestinian people who have been colonized by Israel. Through a literature review and data analysis, this article explores the factors that influence consumers' intentions to switch from foreign to local brands in the context of the boycott phenomenon. When viewed through the consumer literature, there is a significant influence on the intention to switch from foreign brands such as McDonald's or KFC to local brands such as D'kriuk or Sabana. The results of this study are expected to provide valuable insights for fast food industry stakeholders in dealing with the challenges faced by the boycott phenomenon and strategies to maintain consumer loyalty. Keywords: Switching Intention, Boycott Intention, Alternative Attractiveness